Phenolic esters with potential anticancer activity - the structural variable - Machado, Nelson F. L. (2007)
The conformational preferences of several potential anticancer dihydroxycinnamic esters with a variable length alkyl chain were studied by quantum-mechanical (DFT) calculations (both for the isolated molecule and for aqueous solutions). The orientation of the hydroxyl ring substituents and of the alkyl ester moiety relative to the carbonyl group showed these to be the most determinant factors for the overall stability of this type of phenolic systems, strongly dependent on an effective pi-electron delocalization. Compared to the parent caffeic acid (dihydroxycinnamic acid), esterification was found to lead to a higher conformational freedom, and to affect mainly the energy barrier corresponding to the (O=)C-OR internal rotation. No particular differences were verified to occur upon lengthening of the ester alkyl chain, except when this is branched instead of linear. The vibrational spectra of the whole series of compounds were simulated, based on their calculated harmonic vibrational frequencies, and a preliminary assignment was performed.